THE INFLUENCE OF MARKETING MIX TO PATIENT SATISFACTION IN HOSPITALS: NARRATIVE REVIEW - Nurul Qosimah Batubara; Adik Wibowo (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Hospitals, as service providers, have a large role in meeting people's needs regarding their health. The increasing growth of hospitals adds to the menu of choices for people to utilize health services according to their needs. This competition has changed the mechanism by which customers are not only users of health services but as determinants of the future and the continuity of a hospital. Marketing activities can help hospitals improve and win the competition. Marketing managers must be able to combine the marketing mix variables appropriately so that all variables can increase consumer's decision and patient satisfaction. Aims. The purpose of this study was to determine the effect of mix marketing on patient satisfaction at the hospital. Method: This study was conducted in a literature review by searching for articles and journals related to hospital mix marketing. Search journal articles are done through Google Scholar database with the search year 2010 until 2018. The keywords used are